Factors Influencing the Willingness of Hospitalized Children’s Parents to Engage in Patient Safety: A Cross-Sectional Study - Kim Y; Chang M (Risk Management and Healthcare Policy)
Yujeong Kim,1,* Mingi Chang2,* 1College of Nursing, Research Institute of Nursing Innovation, Kyungpook National University, Daegu, Republic of Korea; 2College of Nursing, Kyungpook National University, Daegu, Republic of Korea*These authors contributed equally to this workCorrespondence: Mingi Chang, College of Nursing, Kyungpook National University, 680 Gukchabosangro, Jung-Gu, Daegu, Republic of Korea, 41944, Tel +82-10-6612-9192, Fax +82-53-425-1258, Email mingi4313@naver.comBackground: Hospitalized children’s patient safety incidents can have a significant long-term impact on their physical, psychological, cognitive, and social development. Family-centered care emphasizes engaging parents, and parental involvement is an effective way to ensure child safety. This study aims to identify the factors influencing parents of children with hospitalization experiences in their willingness to engage in patient safety.Methods: In this cross-sectional study, we surveyed 210 parents whose children had been hospitalized within the past one year in South Korea. We used a structured questionnaire including patient safety knowledge, patient safety literacy, children’s hospitalization experience, and the willingness to engage in patient safety. The collected data were analyzed using descriptive statistics, t-test, chi-square test, analysis of variance, correlational analysis, and regression analysis.Results: The willingness to engage in patient safety had significant positive correlations with patient safety knowledge (r=0.36, p